Pentingnya Kesadaran Kewarganegaraan Dalam Masyarakat - Dhea Zahratul Jannah; Depikral Putra Utama; Gita Yuliska; Lisa; Nurul Hanum (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
This writing aims to find out citizenship education in Indonesia on The present era. This civic education is responsible for building the character of the nation Indonesia so that Indonesian citizens can be good, intelligent, and virtuous in accordance with Pancasila. This civic education is very important in the level of education, starting from elementary school To college. However, citizenship education in this younger generation experienced Decline. The lack of moral ethics of good manners is a turmoil in current conditions. Therefore, Education Citizenship depends not only on the school or campus environment, but also on the environment Home to the wider community so that the younger generation can apply this citizenship education In daily life in accordance with the values of Pancasila.